Effect of Using High Protein Level in the First Week of Age on Some Productive Traits of Quail - Taher, Rafh Mohammed (Journal of agricultural, environmental and veterinary sciences, 2018)
This experiment was conducted on 90-day old unsexed brown quail chicks. Chicks divided into three treatments, each one consists of three replicates by ten birds, that were reared in wooden cages for the duration of the experiment. Treatments of the experimental diet consisted of (1) control group containing 26% crude protein during the period 0-3 weeks. Groups (2) and (3) treatments were given a diet containing 28% and 30% crude protein, respectively, during the first week only then 26% protein during the period 2-3 weeks. All the treatments received the same finisher diet containing 24% crude protein, during 4-6 weeks, all starter and finisher diets contains 2, 900 kilocalories/kg ME. The results showed that treatment (2) had significantly (P <0. 05) heavy body weight at 2-week age and best daily and total weight gain, best feed conversion, best protein conversion, and best relative growth coefficient during 0 –2 weeks, while there was no significant effect during other periods, and there was no significant difference between treatments in daily or total feed or protein consumption at any period.